Functional connectivity correlates of response inhibition impairment in anorexia nervosa. (30th January 2016) - Collantoni, Enrico; Michelon, Silvia; Tenconi, Elena; Degortes, Daniela; Titton, Francesca; Manara, Renzo; Clementi, Maurizio; Pinato, Claudia; Forzan, Monica; Cassina, Matteo; Santonastaso, Paolo; Favaro, Angela
Abstract: Anorexia nervosa (AN) is a disorder characterized by high levels of cognitive control and behavioral perseveration. The present study aims at exploring inhibitory control abilities and their functional connectivity correlates in patients with AN. Inhibitory control – an executive function that allows the realization of adaptive behavior according to environmental contingencies – has been assessed by means of the Stop-Signal paradigm. The study involved 155 patients with lifetime AN and 102 healthy women. A subsample underwent resting-state functional magnetic resonance imaging and was genotyped for COMT and 5-HTTLPR polymorphisms. AN patients showed an impaired response inhibition and a disruption of the functional connectivity of the ventral attention circuit, a neural network implicated in behavioral response when a stimulus occurs unexpected. The 5-HTTLPR genotype appears to significantly interact with the functional connectivity of ventral attention network in explaining task performance in both patients and controls, suggesting a role of the serotoninergic system in mechanisms of response selection. The disruption of the ventral attention network in patients with AN suggests lower efficiency of bottom-up signal filtering, which might be involved in difficulties to adapt behavioral responses to environmental needs. Our findings deserve further research to confirm their scientific and therapeutic implications. Highlights: Acute anorexia nervosa patients display impaired response inhibition. Acute anorexia nervosa patients show aberrant functional connectivity of the right inferior frontal gyrus (ventral attention network). 5-HTTLPR genotype appears to significantly interact with the functional connectivity of ventral attention network in explaining task performance in both AN patients and healthy women.